Parate Execution of Dependent Rights Categorized as Unlawful Acts - Kusuma Wardhani, Zakiya (Universitas Islam Malang, 2024)
Abstract : The purpose of this study is to analyze how the implementation of parate execution of dependent rights according to Law Number 4 of 1996 concerning Dependent Rights and why parate execution of dependent rights carried out without permission from the District Court is categorized as unlawful acts. The method used in this study is using normative juridical research methods, using legal approaches and conceptual approaches. The results of this study show that: first, the implementation of parate execution of collateral auctions bound by dependent rights based on Chapter 1 number 28, Chapter 44 paragraphs (1), (2), (3), (4) and Chapter 45 of the Minister of Finance Regulation Number: 27 / PMK.06 / 2016 dated February 22, 2016 concerning Auction Implementation Guidelines for parate auctions of collateral rights execution based on the Law on Dependent Rights, There is an